An introduction to the International Criminal Court - Schabas, William. 1950- (Cambridge ; New York : Cambridge University Press, 2004)
"War criminals have been prosecuted at least since the time of the ancient Greeks, and probably well before that. The idea that there is some common denominator of behaviour, even in the most extreme circumstances of brutal armed conflict, confirms beliefs drawn from philosophy and religion about some of the fundamental values of the human spirit"--
Creation of the court -- The Court becomes operational -- Jurisdiction -- Triggering the jurisdiction -- Admissibility -- General principles of criminal law -- Investigation and pre-trial procedure -- Trial and appeal -- Punishment -- Victims of crimes and their concerns -- Structure and administration of the court.
Includes bibliographical references and index.
Keywords: International Criminal Court; International criminal courts -- Netherlands -- Hague